78.3k views
2 votes
(x/(x+1) + 1)*((1+x)/(2x-1))

User Diaa Saada
by
5.0k points

2 Answers

7 votes

Answer:

=(2x+1) (3x-1)/ (x+1) (2x-1)

=3x-1/ x+1

User Thomas Grady
by
5.6k points
5 votes

Answer:

No solution

Explanation

Combine 1/2 and x

x/2 + 1/2x = x + 1

Combine 1/2 and x

x/2 + x/2 = x + 1

Add x/2 and x/2

2(x/2) = x + 1

Cancel the common factor of 2

Cancel the common factor

(x) = x + 1

Move all terms containing x to the left side of the equation

Subtract x from both sides of the equation

x - x = 1

Subtract x from x

0 = 1

Since 0 ≠ 1, there are no solution

User Daniel Szalay
by
5.2k points